2009
DOI: 10.1021/ja9004656
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate S-Oxygenation Controls Nitric Oxide (NO) Photolability of a Synthetic Iron Nitrile Hydratase (Fe-NHase) Model Derived from Mixed Carboxamide/Thiolate Ligand

Abstract: In order to determine the origin of the NO photolability of the active site of Fe-containing nitrile hydratase (Fe-NHase), a model complex of the NO-bound active site (dark form) has been isolated and structurally characterized. The model, NEt(4)[(Cl(2)PhPepS)Fe(NO)(DMAP)] (2), is derived from a tetradentate ligand comprising carboxamido N and thiolato S donor centers much like the donors present in the active site of Fe-NHase. This {Fe-NO}(6) nitrosyl effectively mimics the NO-bound active site in terms of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…It is concluded that the most possible electronic structure for 1-TPA, 2-iPr PDI and 4-PyImiS is {Fe III (NO -) 2 } 9 . [25,34,35]. These results may imply that NO-to-Fe σ-bonding interaction dominates in the cationic sixcoordinate {Fe(NO) 2 } 9 DNIC 1-TPA.…”
Section: Magnetic Susceptibilitymentioning
confidence: 83%
“…It is concluded that the most possible electronic structure for 1-TPA, 2-iPr PDI and 4-PyImiS is {Fe III (NO -) 2 } 9 . [25,34,35]. These results may imply that NO-to-Fe σ-bonding interaction dominates in the cationic sixcoordinate {Fe(NO) 2 } 9 DNIC 1-TPA.…”
Section: Magnetic Susceptibilitymentioning
confidence: 83%
“…78 A tetradentate bis(arylamido), bis(arylthiolato) ligand was employed (Scheme 21), similar to that of [Fe III (N 2 S 2 )Cl] previously described by Artaud and co-workers. 51 Substitution of Cl − for dimethylaminopyridine (DMAP) afforded the intermediate-spin iron(III) ( S = 3/2) complex [Fe III (Cl 2 PhPepS)(DMAP)] − .…”
Section: Synthetic Models Of S-oxygenation By Other Oxidantsmentioning
confidence: 99%
“…S-Oxygenation by an oxaziridine derivative has also been described by Mascharak and co-workers. 78 A tetradentate bis-(arylamido), bis(arylthiolato) ligand was employed (Scheme 21), similar to that of [Fe III (N 2 S 2 )Cl] previously described by Artaud and co-workers. 51 50 and the reaction of a related complex with H 2 O 2 was also reported (Scheme 22).…”
Section: Synthetic Models Of S-oxygenation By Other Oxidantsmentioning
confidence: 99%
“…Other structures make use of porphyrins as a bulky ligand in order to stabilize the nitric oxide group, and an axially bound NO on cobalt porphyrins with the formula (T( p / m -X)PP)Co(NO) ( p / m -X = p -OCH 3 , p -CH 3 , m -CH 3 , p -H, m -OCH 3 , p -OCF 3 , p -CF 3 , p -CN) [118, 119], and with a ruthenium metal [120, 121]. Photoliability studies on mixed-type structures with both S and N ligands were also examined [122, 123]. X-ray absorption spectroscopic study of nitric oxide binding to iron in active sites was also reported [124].…”
Section: Mononitrosyl and Trinitrosyl Complexesmentioning
confidence: 99%